(untitled) (Research, Society and Development, 2021)
Mother breast-feeding is essential for the child’s nutrition, development and healthy growth, and for the mother there are also great benefits, this act should be something pleasurable, during mother breast-feeding a great connection between mother and child is formed, but for that connection to be formed it is necessary for the mother to feel safe and comfortable, and for the child to suck the milk properly, the wrong handle can cause great discomfort for the mother, thus causing trauma at the time of mother breast-feeding, which can cause early weaning, so to prevent this to happen the nurse has an important performance in the guidance and assistance both in prenatal care and immediate post-birth. The study aims to analyze the performance of nurses in promoting, encouraging and supporting mothers in breastfeeding. This is an integrative review research that will be carried out by a literature review based on secondary works that address the theme, published in the period from 2015 to 2020. The results found underscore the importance of the nurse concerning the care, guidance and assistance to pregnant women and puerperal women in breastfeeding, this review shows us how essential the presence of nurses is, that their technical and scientific knowledge his human look and training as a professional become essential for these mothers and their babies.